International marketing - Ibeh, Kevin (Henry Stewart Talks, 2012)
Definition and scope, Differences with intra-national marketing, Reasons for increasing prevalence, Key marketing management tasks, Entry and development modes, Winning in international markets, Know why, know how, know what, know who, Reasons for failure
Reviewed at 2019/08/29